Vulnerabilidade e resiliência: fatores de risco e proteção em escolares com necessidades educativas especiais - Murata, Marília Pinto Ferreira (Universidade Federal de São Carlos, 2013)
Resilience has emerged as an important factor in overcoming adversity and reducing the negative effects of unfavorable circumstances, and it was considered a dynamic and contextbound, with emphasis on safety nets and adversities mechanisms that interfere in the development of people. This study has a cross-sectional, and correlational studies, using data collected by census survey or parameterized research. It was identify the relationship between risk, protective and resilience factors among children 06-14 years old with disabilities and/or special educational needs, registered in the first to fifth year of the Public elementary school in the Pontal do Paraná town in the Paraná State, and also attended in the resources rooms and special classes. Also participated in this study, children s parents or guardians (60), and teachers (42). Were listed as main points to be investigated resources and adversities related to: a) personal characteristics (behavior, self-concept and resilience factors) b) family environment (organization and family relationships, socioeconomic status, life events); c) school context (behavior and peer relations, school events stressors and academic performance). For data collection were the following instruments with participants: a) with parents (Characterization Questionnaire for Responsible; Critério de Classificação Econômica Brazil; Strengths and Difficulties Questionnaire - Parent Version; Adverse Events Scale and Scale Quality in family interaction) b) with the child (Resilience Scale, Self- Concept Scale and the Children and Youth Inventory of School Hassles) c) with teachers (Characterization Questionnaire for Teachers, which includes characterization of students and their performance academic, Strengths and Difficulties Questionnaire - Teacher Version). The results Showed average in the family income of up to three minimum wages, financial instability and high adversity and about half of the families were classified as risk factor and 40% of them as a protective factor. Regarding personal factors among children, high prevalence of behavioral/mental health, both in the evaluation of parents as teachers, levels of self classified as low or high in about 30% of children; indices of factors resilience average level for most of them. In the school environment was observed high rate of adverse school. In the according to teacher assessment, three-quarters of students participating, showed low academic performance, with a high percentage of learning disabilities and high repetition rate. It was found a significant correlation between levels of resilience and variables related to behavioral problems/mental health, adverse events, family quality interaction and social self-concept. The results indicate a high rate of children at risk in several areas studied and possible protective factors related to resilience, pointing out the importance of this construct gets to work with children with special educational needs, assisting in the reflection and propose actions aimed to minimize the effects of these problems and maximize the aspects of protection for this population.
Keywords: Educação Especial; Resiliência; Fatores de risco e proteção; Necessidades especiais; Inclusão escolar; Necessidades educativas especiais; Resilience; Risk and protective factors; Special educational needs; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL